Implementation Of Make A Match Cooperative Model And Real Media To Improve Poetry Writing Skills At Elementary School Students - sudarsri lestari; Erisy Syawiril Ammah; Eka Ramiati; Atiqatul Musyarofah (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2026)
Abstract   This research aims to determine the improvement in poetry writing results of fifth-grade elementary school students by implementing the make-a-match cooperative model and real media. The research used is classroom action research, employing the Kemmis and Taggart design. The research was carried out in 2 cycles; each cycle consisted of planning, action, observation, and reflection. Research Subjects: 28 students. Data collection was carried out through observation and poetry-writing tests. The research results show that applying the make-a-match cooperative model with real media can improve students' poetry-writing skills. In cycle I, the percentage of students who achieved completeness were 42.86%. In cycle II the number of students who achieved completeness was 71.43%.